2014
DOI: 10.1080/08351813.2014.871804
|View full text |Cite
|
Sign up to set email alerts
|

Asking to Speak to Another: A Skill for Soliciting Survey Participation

Abstract: This paper is in the vein of applied conversation analysis, dealing with a problem of declining participation rates for survey interviews. When calling a household to request participation in a survey, interviewers may ask for a pre-selected “sample person.” We first explore how interviewers design this request in a more or less presumptive way, depending on how and when they identify themselves. Secondly, we analyze different linguistic structures that embody degrees of entitlement. Thirdly, we examine greeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…They also revealed that the order in which interviewers presented information matters: Interviewers' identifying themselves or their institution before asking to speak with the sample member increased agreement to participate (see also Maynard & Hollander, 2014). But the larger story is how interactive the effects are: Actions of the sample member, and how the interviewer responds to those actions, lead to different pathways that invitation sequences might take.…”
Section: Being Invited To Participate In Surveysmentioning
confidence: 90%
See 1 more Smart Citation
“…They also revealed that the order in which interviewers presented information matters: Interviewers' identifying themselves or their institution before asking to speak with the sample member increased agreement to participate (see also Maynard & Hollander, 2014). But the larger story is how interactive the effects are: Actions of the sample member, and how the interviewer responds to those actions, lead to different pathways that invitation sequences might take.…”
Section: Being Invited To Participate In Surveysmentioning
confidence: 90%
“…Detailed examination of the interactions revealed that certain kinds of interviewer speech were associated with a sample member’s increased odds of agreeing to participate, for example, more formal greeting tokens (“hello” vs. “hi”), more politely worded requests (using “may I,” “please,” and the sample member’s first and last name or title plus last name), and the judicious use of mitigators (“just” or “might”) and continuers (“mm-hmm”). They also revealed that the order in which interviewers presented information matters: Interviewers’ identifying themselves or their institution before asking to speak with the sample member increased agreement to participate (see also Maynard & Hollander, 2014). But the larger story is how interactive the effects are: Actions of the sample member, and how the interviewer responds to those actions, lead to different pathways that invitation sequences might take.…”
Section: Being Invited To Participate In Surveysmentioning
confidence: 99%
“…By contrast, in all subsequent calls, switchboard requests feature as part of the call opening. Our analysis in this section also highlights the difference in the designs of switchboard requests (Maynard & Hollander, 2014) in first-time and subsequent calls.…”
Section: Opening the Callmentioning
confidence: 92%
“…With respect to the impact of the interviewer’s actions, Campanelli, Sturgis, and Purdon (1997) reported that participation is more likely when interviewers introduce themselves in face-to-face interviews, but they do not examine where the “introduction” is located or the structure of the first turn. Maynard, Freese, and Schaeffer (2010), Schaeffer et al (2013), Maynard and Hollander (2014), and Nolen and Maynard (2013) analyzed various actions and features of action during the recruitment call for WLS but did not focus on the first turns.…”
Section: Background and Motivationmentioning
confidence: 99%
“…The coding of actions in the interviewer’s first turn extended codes previously developed (Schaeffer et al 2013; Maynard and Hollander 2014). Table 2 summarizes these measures, some of which are complementary or dependent in other ways.…”
Section: Datamentioning
confidence: 99%